Clean And Healthy Living Behavior (Phbs) With The Incidence Of Scabies In School-Age Children In Mas Assasunnajah, Aceh Besar District - Najikhah, Nur; Hidayattullah, Mhd.; Putri, Rosalia; Putri, Natasha Aulia (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2023)
Health problems, especially those related to clean and healthy living behavior, are prone to occur in school-aged children. Some diseases that are often found in school-aged children include scabies, diarrhea and dengue fever. Prevention of this problem can be done through a clean and healthy living behavior program. Indicators of clean and healthy living behavior in educational institutions/schools include washing hands with running water and using soap, consuming healthy snacks in the school canteen, using clean and healthy latrines, exercising regularly and in a measured manner, eradicating mosquito larvae, not smoking at school. , weigh and measure height, and dispose of rubbish in the right place. The aim of this study was to determine clean and healthy living behavior and the incidence of scabies in school-aged children. The research method uses a quantitative method with a cross sectional approach, the samples used in this research were 62 samples, then data processing used SPSS. The research results showed that clean and healthy living behavior was related to the incidence of scabies (0.001). Based on the research results, it can be concluded that PHBS is related to the incidence of scabies.